Robberies in Chicago, 1982-1983 - Zimring, Franklin E. ([Verlag nicht ermittelbar], 1989)
This study investigates the factors and conditions in robbery events that cause victim injury or death. The investigators compare three robbery events: those that resulted in death, those that cause injury, and nonfatal robberies of all types. The events were compared on a variety of demographic variables. The data address the following questions: (1) To what extent are homicides resulting from robbery misclassified as homicides for which motives are undetermined? (2) How often do homicides resulting from robbery involve individuals who do not know each other? (3) Are robberies that involve illicit drugs more likely to result in the death of the victim? (4) To what extent does a weapon used in a robbery affect the probability that a victim will die? (5) To what extent does victim resistance affect the likelihood of victim death? (6) To what extent does robbery lead to physical injury? (7) Do individuals of different races suffer disproportionately from injuries resulting from robbery? (8) Are injuries and homicides resulting from robbery more likely to occur in a residence, commercial establishment, or on the street? (9) Are women or men more likely to be victims of homicide or injury resulting from robbery? (10) To what extent does robbery (with or without a homicide) occur between or within races? (12) How long does it take to solve robbery-related crimes? Major variables characterizing the unit of observation, the robbery event, include: location of the robbery incident, numbers of offenders and victims involved in the incident, victim's and offender's prior arrest and conviction histories, the extent of injury, whether or not drugs were involved in any way, type of weapon used, victim/offender relationship, and the extent of victim resistance.